2017
DOI: 10.1176/appi.ps.201600377
|View full text |Cite
|
Sign up to set email alerts
|

A 60-Week Prospective RCT of a Self-Management Intervention for Individuals With Serious Mental Illness and Diabetes Mellitus

Abstract: Objectives Targeted Training in Illness Management (TTIM) addresses serious mental illness and diabetes (DM) concurrently and is designed to improve psychiatric symptoms, functioning, general health and DM control. This 60-week, randomized controlled trial assessed TTIM vs. treatment as usual in 200 individuals with serious mental illness and diabetes. Methods Clinical Global Impression (CGI), Montgomery Asberg Depression Rating Scale (MADRS) and Brief Psychiatric Rating Scale (BPRS) assessed symptoms. Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 43 publications
(41 reference statements)
0
62
0
Order By: Relevance
“…Exploring the reasons for our search strategy's failure to identify these two studies, we found that one had actually been retrieved, but had mistakenly been excluded in the screening of titles and abstracts, probably because of its focus on comorbid anxiety [27]. The other study had probably been excluded because the abstract referred only to diabetes self-care activities as 'DM [diabetes mellitus] control' [28].…”
Section: Literature Search and Selection Of Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the reasons for our search strategy's failure to identify these two studies, we found that one had actually been retrieved, but had mistakenly been excluded in the screening of titles and abstracts, probably because of its focus on comorbid anxiety [27]. The other study had probably been excluded because the abstract referred only to diabetes self-care activities as 'DM [diabetes mellitus] control' [28].…”
Section: Literature Search and Selection Of Sourcesmentioning
confidence: 99%
“…Of the four interventional studies, one aimed to test the effects of a lifestyle intervention among people with type 2 diabetes and schizophrenia [46], two tested the effects of a group-based psychosocial treatment among people with type 2 diabetes and various severe mental illnesses [27,28], and one aimed to test the effects of antidepressant medications among people with type 2 diabetes and major depression [47].…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…SMART is an adjunct to standard epilepsy care that is largely similar to the TIME approach and is informed by chronic disease self-management principles and techniques. [9][10][11] Consistent with community-based participatory research principles, TIME was refined with iterative input from a 13-member community advisory board (CAB) composed of individuals with epilepsy (n = 6 including one veteran), family members (n = 4), Veterans Administration and safety net clinicians (n = 2), and Prevention Research Center's Network of Community Advisors (n = 1). Mean CAB participant age was 49.6 years (SD = 10.1, range = 32-64); there were seven women and six men.…”
Section: Smart Interventionmentioning
confidence: 99%
“…MEW Network investigators at the Case Western Reserve University Prevention Research Center used an iterative, collaborative process to adapt an existing manualized intervention initially developed for people with serious mental illness and comorbid diabetes, [17, 18] and tested the adapted intervention, T argeted Self-Management for Ep i lepsy and Me ntal Illness (TIME) for feasibility, acceptability and preliminary efficacy in people with E-MI, using a prospective randomized controlled design comparing TIME vs. treatment as usual (TAU) over a 16-week time period in individuals with E-MI. The primary hypothesis was that at 16 weeks, TIME would be associated with greater improvement in depressive symptoms, as assessed by the Montgomery Asberg Depression Rating Scale (MADRS), compared to TAU.…”
Section: Introductionmentioning
confidence: 99%